The breath of my life: constructing the self in chen ran’s A private life - Hardenberg, Wendeline A (Women's Studies, 2014)
Keywords: dept.lib

Will You Ever Change? Translated by Wendeline Hardenberg - Valognes, Aurélie (Amazon Crossing, 2017)
Charming, quirky, and funny, this oh-so-relatable novel from the bestselling author of Out of Sorts shines a light on the always-complicated je ne sais quoi of every family’s relationship.As Martine and Jacques Le Guennec prepare for their annual family Christmas dinner, Martine reminds her husband to be on his best behavior. Their son Nicolas is bringing his girlfriend, Jeanne, to their home for the first time, and she doesn’t want Jacques to scare this one off.Jacques has always ruled his roost with patriarchal bravado, and he can’t help but verbally antagonize everyone—especially the wives of his sons. Jeanne, a strong-willed woman who grew up without a father, clashes with the curmudgeon, and she worries that her boyfriend might be too much like his father.It’s all starting to make Martine question everything about her relationship with her husband. And, though she makes that perfectly clear to him, the old dog is not anxious to learn new tricks.When Jeanne saves Jacques’s life, he begins to realize it may be time to change his ways if he wants to hold on to his wife and keep the family close. But is it too late?
Keywords: dept.lib

Contemporary Art is Internationally Appealing by Vincent Ravalec, translated by Wendeline A. Hardenberg - Gaffey, Marlee (Tupelo Quarterly, 2018)
The challenge was to make appealing something that was not. To transform this godforsaken city, populated by people as indifferent to art as tourists are to the idea of visiting the only historic building—a vague ruin of a castle—in a glamorous destination. After all, what the Guggenheim did for Bilbao could be reproduced […]
Keywords: dept.lib

Persephone 2014 Translated by Wendeline Hardenberg - Aubry, Gwenaëlle (Asymptote, 2019)
Keywords: dept.lib

The Matrix and the Machine Translated by Wendeline Hardenberg - Ravalec, Vincent (Asymptote, 2018)
Keywords: dept.lib

Project Anastasis Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2016)
As a former soldier, private investigator Jean Legarec is used to high stakes and sharpshooters. But he doesn’t realize what he’s getting into when he agrees to investigate the disappearance of six-year-old Alexandre, the grandson of a highly influential French politician.For a million euros, Legarec launches a dangerous search that will dig deep into some of the darkest corners of European history. With the help of the boy’s beautiful aunt, Béatrice, he uncovers evidence of a modern-day terrorist plot rooted in a long-buried enterprise of the Third Reich. From Paris to Malta to the Vosges forest, a cast of witnesses—including a death camp survivor and former mercenaries—help Legarec piece together a terrifying truth.Yet even then, the PI worries that his own dark past and his undeniable attraction to Béatrice might be clouding the investigation. Can he put the personal aside in order to do his job? And can he free an innocent child from a web of absolute evil?
Keywords: dept.lib; faculty_collection

Out of Sorts Translated by Wendeline Hardenberg - Valognes, Aurélie (Amazon Crossing, 2016)
Ferdinand Brun hasn’t always been a grumpy old man. Many years ago, he was a grumpy young man. Now he’d much rather spend time with his canine companion, Daisy, than any of his nosy neighbors. But as his behavior becomes increasingly peculiar, his daughter grows concerned and begins to consider moving him into a retirement home.In order to maintain his freedom, Ferdinand must submit to an apartment inspection by his longtime enemy, the iron-fisted concierge, Mrs. Suarez. Unfortunately, he’s never tidied up a day in his life. His neighbors, precocious ten-year-old Juliette and vivacious ninety-two-year-old Beatrice, come to the rescue. And once he lets these two into his life, things will never be the same. After an eighty-three-year reign of grouchiness, Ferdinand may finally learn that it’s never too late to start living.
Keywords: Aging; Fiction; Fiction; Families; Fiction; France; Fiction; Man-woman relationships; dept.lib; faculty_collection

Heart Collector Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2015)
Finding murderers is just a day on the job for police captain Nadia Barka. But when a mutilated corpse is discovered in an old baptistery, she’s faced with some difficult questions: Who left a young woman’s body in a high-security museum in the middle of the night? And where is the victim’s heart?Barka has no leads, until several days later when unassuming computer technician Julien Lombard comes forward, claiming to have had a premonition of the woman’s abduction and murder. The ensuing investigation turns up nothing, however, and Julien is just as skeptical about his intel as the police are. But, after another woman goes missing, Barka decides to take a chance and trust in Julien’s gift. Does Julien hold the key to preventing another gruesome crime? Working together, can they find the murderer before he steals another heart?
Keywords: dept.lib; faculty_collection

Badadoom Badabump! Translated by Wendeline Hardenberg - Baou, Bartélémi (Twirl Books, 2019)
Inspiring imagination and encouraging hours of creative play, Badaboom Badabump! is an innovative play set that not only includes a …
Keywords: dept.lib

Jungle Animals Translated by Wendeline Hardenberg - Mazas, Marie (Twirl Books, 2019)
The shaggy fur of a sloth, the scaly skin of an iguana, and the rough hide of a tapir—there’s so …
Keywords: dept.lib

Astronauts Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Count down to an incredible voyage! • Learning to pilot a spacecraft • Getting used to being weightless • Going …
Keywords: dept.lib

Pirates Translated by Wendeline Hardenberg - Adams, Ines (Twirl Books, 2019)
Heave ho! Set sail on a high-seas adventure with swashbuckling pirates in search of treasure in this new Magnetology™ title. …
Keywords: dept.lib

Baby Animals Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Keywords: dept.lib

Body Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Big, sturdy tabs to push and pull make for great learning fun in this brand-new nonfiction series. Preschool children learn …
Keywords: dept.lib

Yoga Together! Translated by Wendeline Hardenberg - Jouanne, Elisabeth (Twirl Books, 2019)
Keywords: dept.lib

Cars Translated by Wendeline Hardenberg - Krasinski, Geraldine (Twirl Books, 2019)
Turn a wheel to see cars of yesteryear, slide a new car onto a car carrier, pull a tab to …
Keywords: dept.lib

Super Mazes in Space! Translated by Wendeline Hardenberg - Méhée, Loïc (Twirl Books, 2019)
Ten incredible mazes combine with a space adventure to provide a stellar game book for every puzzle-solving kid! Comics artist …
Keywords: dept.lib

Construction Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Bumpy roads, rough wood beams, and smooth concrete—there’s so much to discover in this Touch and ExploreTM book that’s all …
Keywords: dept.lib

Who Lives Where? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Sliding panels of animals near and far make for a delightful and satisfying format for matching game fun! Each of …
Keywords: dept.lib

Will You Ever Change? - Valognes, Aurélie (Amazoncrossing, 2017)
Keywords: Domestic fiction, French; dept.lib; faculty_collection

"Words" Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (One Sentence Poems, 2018)
Keywords: dept.lib

[Six Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Metamorphoses: Journal of the Five-College Seminars on Literary Translation, 2013)
Keywords: dept.lib; ⛔ No DOI found

[Two Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Absinthe: New European Writing, 2018)
Keywords: dept.lib; ⛔ No DOI found

[Three Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Asymptote, 2012)
Keywords: dept.lib

[Five Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (TWO LINES Online, 2012)
Keywords: dept.lib

[Seven Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (The Dirty Goat, 2011)
Keywords: dept.lib

Max Ernst Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Qarrtsiluni Online Literary Magazine, 2011)
Keywords: dept.lib

[Two Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Ozone Park Journal, 2010)
Keywords: dept.lib

Feelings Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
It’s never too early to encourage children to talk about how they feel. This newest title in the Pull and …
Keywords: dept.lib